Analisis Pengelolaan Aset Daerah Dalam Upaya Meningkatkan Kualitas Laporan Keuangan Daerah (Studi Kasus Pada Badan Keuangan dan Aset Daerah Pemerintah Kabupaten Subang) - Anjes Faresh Faisal; Mia Rosmiati (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
Management of regional assets in Subang Regency is still a problem finding for BPK. especially on fixed assets in the form of land and buildings that have not been certified. This study uses a qualitative-descriptive method with data obtained through observation, interviews, and literature studies with the research location at the Regional Finance and Asset Agency. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of the study indicate that the management of regional assets in the Subang Regency Government still has several obstacles, such as the lack of quality in the ability of Human Resources to manage regional property, coordination and communication are not optimal. However, the Subang Regency Government continues to strive to improve the quality of financial reports by providing technical guidance to employees managing goods and continuing to follow up on BPK's findings.